2016
DOI: 10.1186/s12906-016-1185-y
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and evaluation of antibacterial and antiproliferative activities of crude protein extracts isolated from the seed of Ricinus communis in Bangladesh

Abstract: BackgroundRicinus communis (Euphorbiaceae) has previously been reported to possess analgesic, antihistamine, antioxidant and anti-inflammatory activities. This study was designed for isolation, characterization and evaluation of antibacterial and anti-proliferative activities of R. communis seed protein.MethodsThe concentration and molecular weight of R. communis seed protein were estimated by SDS-PAGE and spectrophotometric analysis, respectively. Lectin activity was evaluated by hemagglutination assay on mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 45 publications
1
13
0
1
Order By: Relevance
“…It was observed that the protein profile of fresh ricin seeds showed faint and comparatively light bands in contrast to dried seed samples in which relatively darker bands were observed. In both the protein profiles (fresh and dried seeds) bands ranging from 45kDa to approximate 15kDa were observed which were in accordance with the results as obtained by Al-Mamun et al 9 In the protein profile of fresh seeds, bands of molecular weight of 43kDa, 44kDa, 25kDa, 24kDa, 23kDa, 17kDa, 16kDa, 15kDa, were observed. A similar observation was made in the protein profile of dry ricin seed sample, wherein bands of 43kDa, 44kDa, 25kDa, 24kDa, 23kDa, 17kDa, 16kDa, 15kDa, were observed.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…It was observed that the protein profile of fresh ricin seeds showed faint and comparatively light bands in contrast to dried seed samples in which relatively darker bands were observed. In both the protein profiles (fresh and dried seeds) bands ranging from 45kDa to approximate 15kDa were observed which were in accordance with the results as obtained by Al-Mamun et al 9 In the protein profile of fresh seeds, bands of molecular weight of 43kDa, 44kDa, 25kDa, 24kDa, 23kDa, 17kDa, 16kDa, 15kDa, were observed. A similar observation was made in the protein profile of dry ricin seed sample, wherein bands of 43kDa, 44kDa, 25kDa, 24kDa, 23kDa, 17kDa, 16kDa, 15kDa, were observed.…”
Section: Resultssupporting
confidence: 91%
“…Cannabis ( The quantitative estimation of proteins by Folin's method showed a high concentration of proteins in all the samples as shown in Table 2. The concentration of ricin in case of Ricinus communis seeds was found to be much higher in all the samples as compared to that found by Al-Mamun et al 9 The standard calibration graph for Ricinus communis has been shown in Fig. 7.…”
Section: Resultsmentioning
confidence: 48%
“…In the case of KRL-2 from Kaempferia rotunda , 41% and 59% of EAC cell growth inhibition was found at the doses of 3 mg/kg/day and 6 mg/kg/day [27]. At a fixed concentration of 100 μg/mL, plant extracts with lectin activity from Ricinus communis and Amaranthus hybridus led to 54 and 45% growth inhibition of EAC cells, respectively [35,36]. Considering these results, antiproliferative activity of MytiLec-1 to EAC cells is quite significant despite of its low toxicity to brine shrimp.…”
Section: Discussionmentioning
confidence: 99%
“…Though it passes through the membrane of live cells but the effectiveness of the stain is lower ( Kerr et al, 1972 ). Apoptotic morphological alterations such as fragmented nuclei and nuclear condensation among the neighboring cells have been observed by fluorescence microscopy in treated groups compared to the control group ( Al-Mamun et al, 2016a ). Besides, more condensed and fragmented nuclei have been found in case of MEPA fruit pulp treated EAC cell images rather than the seed extract which may be due to the initiation of EAC cell apoptosis ( Hasan et al, 2019 , Zahan et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%